Sonocatalyzed ammonothermal preparation of fine lithium niobate powders - A. Rujiwatra (2018)
The so-called sonocatalyzed ammonothermal technique has been developed for the preparation of lithium niobate fine powders from commercially as-received niobium pentoxide and lithium nitrate. The present work shows that the application of ultrasonic activation prior to the ammonothermal treatment can produce a single phase lithium niobate fine powder at a relatively low temperature of 220°C. The influences of Li-precursors, ammonia solution concentration, reaction temperature and time, as well as Li:Nb mole ratio - which is evidentially the most critical factor promoting a single phase formation - are discussed. © 2008 Trans Tech Publications, Switzerland.